Understanding the associations between psychosocial factors and severity of crime in juvenile delinquency: a cross-sectional study - Semerci, Bengi; Taskiran, Sarper; Mutluer, Tuba; Tufan, Ali Evren (DOVE MEDICAL PRESS LTD, 2017)
Purpose: Juvenile delinquency is a serious and common problem. To date, several studies have focused on possible psychosocial risk factors for delinquency among youths and on the implications of childhood mental illness on child criminality. However, the literature on prevalence of psychopathology and predictors of crime severity among delinquent youths in Turkey is sparse. Therefore, the aim of this study was to show the associations between crime severity and psychosocial factors such as gender, age, criminal history, concomitant attention deficit hyperactivity disorder (ADHD) and other comorbid psychiatric conditions, along with behavioral problem domains of Child Behavior Checklist (CBCL). Participants and methods: This analytical cross-sectional study sample consisted of 52 individuals (30 females and 22 males) who were sent to a pilot detention facility in Istanbul, Turkey. The participants' age ranged from 8 to 18 years (M = 13.4; SD = 2.9). Self-rating scales were administered in an interview format, and the crime severity information was provided by participants' admission documents. Results: No differences were found in terms of gender, age, children's past history of crime and substance abuse. However, family crime history was significantly higher in the high severity crime group (P=0.026). Having one or more comorbid psychiatric disorder was associated with high crime severity (P=0.018). The most common psychiatric disorders were found to be ADHD, oppositional defiant disorder, conduct disorder (CD) and anxiety disorder. Conclusion: Findings suggest that a family history of crime comes across as a very strong predictor of severity of crime. Among psychiatric factors, ADHD and CD were associated with commitment of more severe crimes in delinquent youths in our sample. Anxious/depressed traits as depicted by CBCL are found to be associated with less severe crimes.
Keywords: crime severity; delinquent behavior; ADHD; conduct disorder; risk factors; juvenile delinquency